Synthesis and NO2 gas-sensing properties of coral-like indium oxide via a facile solvothermal method. Issue 78 (23rd October 2017) - Zhang, Haijiao; Xu, Xiumei; Zhu, Yongsheng; Bao, Keyan; Lu, Zhiwen; Sun, Peng; Sun, Yanfeng; Lu, Geyu
Abstract : In this work, coral-like indium oxide was synthesized via an environmentally friendly one-step solvothermal method and the gas sensing properties were investigated. Abstract : In this work, coral-like indium oxide was synthesized via an environmentally friendly one-step solvothermal method. The as-synthesized samples were characterized using X-ray powder diffraction (XRD), field emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM). The results indicate that the synthesized indium oxide nanorods were formed of nanoparticles. Moreover, the gas sensing properties of the coral-like products were investigated, and they exhibited high response and good selectivity to NO2 .